Potassium supplying capacity of five soils of the submédio São Francisco valley - Faria, Clementino Marcos Batista de; Pereira, José Ribamar (Pesquisa Agropecuaria Brasileira, 2014)
With the objective to evaluate the potassium supplying capacity of five soils of the Submedio São Francisco valley, Pernambuco and Bahia, Brazil, named as Bebedouro 6, Bebedouro 3, Massangano, Mandacaru and Salitre was carried out this experiment in Laboratory and greenhouse. The first three soils are classified as Red Yellow Latosol and the latter two as Non-Calcic-Brown Soil and Vertisol, respectively. Two liters of each soil with and without K, 1.6 g K, was submitted to one cropping with sorghum and five with corn during nine months. Five weeks after seeding the shoots were harvested. The total yield of dry matter (DM) obtained in the treatments that received K varied from 37% to 154% in relation to treatments without K. There were significative correlations of the DM with K absorbed by the plants (r = 0.98**); K extracted by NH4OAC 1N pH 7.0 (r = 0.95*); K extracted by Mehlich solution (r = 0.89*), non exhangeable K released to plants (r = 0.96** ), and no significant correlation (0.87ns) with K extracted by boiling 1N NHO3. The K supplying capacity evaluated through the crops corresponded to 0.23; 0.37; 0.23; 0.32 and 0.56 e.mg/ 100 ml of K for the soils of Bebedouro 6, Bebedouro 3, Massangano, Mandacaru and Salitre, respectively. The K extracted by 1N NH4 OAC, showed highly significant correlation (r = 0.99**) with soil K reserve, because of this, it is considered the best index to evaluate the supplying capacity of these soils.